Bone marrow pathology - Bain, Barbara J.; Clark, David M. , MD; Wilkins, Bridget , 1959- (Wiley-Blackwell, 2010)
Shows the advances which have occurred in the application of cytogenetics and in particular, molecular genetics in the diagnosis, classification and understanding of haematological disorders. This book provides information on common disease entities, and also covers rare disorders in which bone marrow examination is useful.